Amygdala subnuclei resting-state functional connectivity sex and estrogen differences. (January 2016) - Engman, Jonas; Linnman, Clas; Van Dijk, Koene R.A.; Milad, Mohammed R.
Highlights: We study amygdala resting-state connectivity in relationship to sex and estrogen. The laterobasal (LB) and centromedial (CM) amygdala subnuclei were used as seeds. Distinct connectivity patterns were seen between the sexes and estrogen levels. These are potentially valuable in explaining sex differences in negative affect. The results also support control for sex in amygdala related resting-state studies. Abstract: The amygdala is a hub in emotional processing, including that of negative affect. Healthy men and women have distinct differences in amygdala responses, potentially setting the stage for the observed sex differences in the prevalence of fear, anxiety, and pain disorders. Here, we examined how amygdala subnuclei resting-state functional connectivity is affected by sex, as well as explored how the functional connectivity is related to estrogen levels. Resting-state functional connectivity was measured using functional magnetic resonance imaging (fMRI) with seeds placed in the left and right laterobasal (LB) and centromedial (CM) amygdala. Sex differences were studied in 48 healthy men and 48 healthy women, matched for age, while the association with estrogen was analyzed in a subsample of 24 women, for whom hormone levels had been assessed. For the hormone analyses, the subsample was further divided into a lower and higher estrogen levels group based on a median split. We found distinct sex differences in the LB and CM amygdala resting-state functional connectivity, as well as preliminary evidence for an association between estrogen levels and connectivity patterns. These results are potentially valuable in explaining why women are more afflicted by conditions of negative affect than are men, and could imply a mechanistic role for estrogen in modulating emotion.